Twist analysis of piezoelectric laminated composite plates - Khan, Md. Raisuddin; Mahmood, Iskandar Al-Thani (2006)
Recently scientists are showing interests in smart structures for their capability in controlling structural behavior and monitoring structural health. Twist control of helicopter rotors, micromirrors or shafts in torsional oscillation are the active areas of research where smart materials like piezoceramic crystal or shape memory alloy can play vital roles. In this paper analysis of twisting of piezoelectric laminated composite plates using higher order shear deformation theory has been presented.